A novel hybrid space vector-based modulation technique for power quality improvement in a wind energy conversion system. (7th September 2020) - Boopathi, R.; Jayanthi, R.; Ansari, M. Mohamed Thameem
The paper develops a novel hybrid space vector pulse width modulation (HSVPWM) for improving the quality of power transfer from a permanent magnet synchronous generator (PMSG) based wind energy conversion system (WECS) to a three phase induction motor load. It includes a Vienna rectifier (VR) based ac-dc converter in the front end and a voltage source inverter (VSI) for providing the variable frequency, variable voltage requirements of the induction motor load. The Vienna rectifier attempts to offer almost a unity power factor and early sinusoidal input as the input to the VSI as part of resurrecting the shape of the supply side waveform to the motor. The formulation involves a three-phase three-level HSVPWM along with a novel hysteresis current control technique for generating the firing pulses to the power switches in the VSI. The simulation results reveal a higher fundamental component a lower total harmonic distortion (THD) and harmonic spread factor (HSF) for the inverter output voltage over the similar other pulse width modulation (PWM) schemes and allow it claim a space for its use in real world utilities.